Digital collected letters: the transformation of letters to digital environment - Ramírez Martín, Virginia (Revista General de Información y Documentación, 2017)
From several decades ago, the scientific value of collected letters has revealed itself as an essential piece to progress in several fields of research, as well as a key tool to rebuilt its inner-history in every time. However, the present situation poses several problems in relation with this type of document collection, both documents in the middle of transition to digital stage and some of them changed thoroughly. Not only they have been diversified themselves hugely in consequence of technologic development and essential change suffered from tool for communicating, but also they pose a lot of doubts about its preservation and treatment. The present article tries to get closer to complexity of these materials and highlights their inestimable value from future research is yet to come.